Financial System Structure in Colombia : A Proposal for a Reform Agenda - De la Cruz, Javier; Stephanou, Constantinos (World Bank, Washington, DC, 2012)
The objective of this policy paper is to identify and propose high-level legal and regulatory reforms to Colombia's financial system structure that would enhance efficiency and/or mitigate risks. Five specific and four general reforms are proposed and evaluated based on their compatibility with the aforementioned objectives, ease of implementation, impact, and consistency with international practice. Potential implications for supervision and competition, as well as likely criteria for developing a carefully sequenced reform roadmap, are also highlighted.